Concepciones de tecnología en docentes universitarios de ciencias - Cardoso-Erlam, Néstor Roberto; Morales-Oliveros, Edna Eliana (Revista Científica, 2017)
Next, it´s a partial result of the research investigation “Conceptions of sciences, technology and CTS relations with training academic, secondary teachers and sciences textbooks” Then the question about teachers´ conceptions of the nature of technology is that teachers of the University of Tolima expressed is discussed. Information was collected through interviews and focus information analysis was performed using content analysis. It´s found that teachers have different conceptions about the nature of technology some more outdated than others.